Identification and Characterization of Antimicrobial Peptides From Butterflies: An Integrated Bioinformatics and Experimental Study - Wang, Min; Zhou, Ziyue; Li, Simin; Zhu, Wei; Hu, Xianda (Frontiers in Microbiology, 2021)
Butterflies represent one of the largest animal groups on Earth, yet antimicrobial peptides (AMPs) of this group are less studied in comparison with their moth counterparts. This study employed an integrated bioinformatics approach to survey natural AMPs from publicly available genomic datasets. Numerous AMPs, including cecropins, defensins, and moricins, were identified and subsequently used as templates for the design of a series of synthetic AMPs that mimicked the naturally occurring sequences. Despite differing biological effects among the various sequences, the synthetic AMPs exhibited potent antibacterial and antifungal activities in vitro and in vivo, without inducing hemolysis, which implied their therapeutic potential in infectious diseases. Electron and confocal fluorescence microscopies revealed that the AMPs induced distinct morphological and biophysical changes on microbial cell membranes and nuclei, suggesting that the antimicrobial effects were related to a mechanism of membrane penetration and nucleic acid binding by the peptides. In conclusion, this study not only offers insights into butterfly AMPs but also provides a practical strategy for high-throughput natural AMP discoveries that will have implications for future research in this area.